Smoking attitude and behaviour of a public organisation data processing centre workers - Altıntaş, Hakan; Boztaş, Güledal; Polat, Ceren; Salor, Özge; Yaman, İnci and Uğurlu, Esra (Journal of Dependence, 2006)
Objective: This study was conducted to find out the prevalence of smoking, to evaluate the characteristics associated to smoking behaviour and the opinions about the regulations and the acts related to smoking among Data Processing Centre workers. Method: This cross-sectional study was conducted on 190 persons with a 37-item self-administered questionnaire on June, 2005. Results: 48.9% of the participants were men; 44.1% of men and 55.9% of women workers were current smokers respectively. Staring smoking before the age of 17 was 43.9% for men and 11.5% for women (p=0.03). 51.3% of the workers perceived anti-tobacco campaigns’ target as smokers. More than 85% of the participants approved the anti-tobacco act (Act No:4207) and 79.9% of workers thought that The Offences Act must be observed in the work place. Conclusion: Although smoking behaviour wasn’t different between men and women, the difference in smoking commencement age was statistically significant between them. It would be beneficial to allocate a separate room for the smokers, to apply effective stress-management strategies and to dispense adequate information that the antismoking campaign targets smoking itself and health hazards related to smoking.